2008
DOI: 10.1002/pssc.200778336
|View full text |Cite
|
Sign up to set email alerts
|

Highly localized ion focusing effects in PBIID

Abstract: Plasma Based Ion Implantation and Deposition (PBIID) is characterized by a complex interaction of a supersonic plasma flux, a plasma sheath expanding and receding on a timescale of microseconds and a substrate which can be of an arbitrary complex shape. It is shown that ions impinging on the substrate in the wake region consist of two groups with strongly differing incidence angles. At the same time, localized ion focusing is observed only for very long pulses of 50 µs and intermediate voltages of 2.5 – 3.5 kV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Irradiation with 6 MeV Zr +4 is expected to produce random point defects and nm-sized anisotropic defects. Previous irradiation studies of GBCO CCs showed that the optimal dosage to achieve the maximum pinning enhancement at temperatures below 40 K, using either H or O ions are 2×10 16 cm -2 and 1×10 14 cm -2 , respectively [5,7]. However, according to SRIM simulations, the Zr ions will produce significantly more displacements per collision than H or O.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Irradiation with 6 MeV Zr +4 is expected to produce random point defects and nm-sized anisotropic defects. Previous irradiation studies of GBCO CCs showed that the optimal dosage to achieve the maximum pinning enhancement at temperatures below 40 K, using either H or O ions are 2×10 16 cm -2 and 1×10 14 cm -2 , respectively [5,7]. However, according to SRIM simulations, the Zr ions will produce significantly more displacements per collision than H or O.…”
Section: Methodsmentioning
confidence: 99%
“…Artificially designed mixed pinning landscapes seem to be a tool to improve critical current densities J c in high temperature superconductors [1,2,3]. A significant enhancement of the infield J c of RBa 2 Cu 3 O 7−δ (RBCO; R: Sm, Dy, Y, Gd) coated superconductors (CCs) can be obtained by adding pinning centers by ion irradiation [4,5,6,7,8]. For adequate irradiation fluences (which depend on mass and energy of ions), adding small clusters and random disorder assists the pinning produced by normal inclusions and twin boundaries (originated during the synthesis) [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation